ggtranscript: an R package for the visualization and interpretation of transcript isoforms using ggplot2 - Gustavsson, Emil K; Zhang, David; Reynolds, Regina H; Garcia-Ruiz, Sonia; Ryten, Mina (Bioinformatics, 2022)
Abstract Motivation The advent of long-read sequencing technologies has increased demand for the visualization and interpretation of transcripts. However, tools that perform such visualizations remain inflexible and lack the ability to easily identify differences between transcript structures. Here, we introduce ggtranscript, an R package that provides a fast and flexible method to visualize and compare transcripts. As a ggplot2 extension, ggtranscript inherits the functionality and familiarity of ggplot2 making it easy to use. Availability and implementation ggtranscript is an R package available at https://github.com/dzhang32/ggtranscript (DOI: https://doi.org/10.5281/zenodo.6374061) via an open-source MIT licence. Further documentation is available at https://dzhang32.github.io/ggtranscript/.